2009
DOI: 10.1021/jp903813h
|View full text |Cite
|
Sign up to set email alerts
|

Long Electron−Hole Separation of ZnO-CdS Core−Shell Quantum Dots

Abstract: The tunability of electronic and optical properties of semiconductor nanocrystal quantum dots (QDs) has been an important subject in nanotechnology. While control of the emission property of QDs in wavelength has been studied extensively, control of the emission lifetime of QDs has not been explored in depth. In this report, ZnO-CdS core–shell QDs were synthesized in a two-step process, in which we initially synthesized ZnO core particles, and then stepwise slow growth of CdS shells followed. The coating of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…The type-II interfaces between semiconductors caused spatial separation and increased lifetimes of photogenerated excitons, which decreased internal charge recombination (Xu et al 2009). The type-II band alignment formed when one of the two semiconductors has the energy minimum of both CB and VB .…”
Section: Resultsmentioning
confidence: 99%
“…The type-II interfaces between semiconductors caused spatial separation and increased lifetimes of photogenerated excitons, which decreased internal charge recombination (Xu et al 2009). The type-II band alignment formed when one of the two semiconductors has the energy minimum of both CB and VB .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ZnO and Cu 2 S complex films have a good photocatalytic performance. They can completely destruct the undesirable contaminants in both liquid and gaseous phase by using solar or artificial light illumination [12][13]. As we know, the efficiency of photocatalytic reaction is determined by the absorption ability of light and high separation rate of photo-induced electron-hole pair.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductors, such as CdS, are usually combined with ZnO to form hierarchical heterostructures for visible light photocatalytic degradation due to their narrow band gaps [108,[131][132][133]. For example, nanoscale tree-like CdS/ZnO nanocomposites with a hierarchical architecture showed the ability for selective oxidation of thioanisole and anaerobic reduction of nitro compound 4-nitroaniline under irradiation of artificial solar light [108].…”
Section: Photocatalytic Applications Of Hierarchical Zno Nanostructurmentioning
confidence: 99%
“…Especially, Liu et al [90] reported hierarchical flower-like C-doped ZnO superstructures (ZnO flowers) assembled from porous nanosheets, which showed better photocatalytic decomposition of the RhB dye in aqueous solutions than ZnO due to the enhanced light absorption over a wide range of wavelengths. Semiconductors, such as CdS, are usually combined with ZnO to form hierarchical heterostructures for visible light photocatalytic degradation due to their narrow band gaps [108,[131][132][133]. For example, nanoscale tree-like CdS/ZnO nanocomposites with a hierarchical architecture showed the ability for selective oxidation of thioanisole and anaerobic reduction of nitro compound 4-nitroaniline under irradiation of artificial solar light [108].…”
Section: Photocatalytic Applications Of Hierarchical Zno Nanostructurmentioning
confidence: 99%